2003
DOI: 10.1029/2002pa000850
|View full text |Cite
|
Sign up to set email alerts
|

Neogene changes in Southern Ocean sedimentation based on mass accumulation rates at four continental margins

Abstract: High‐resolution mass accumulation rates (MAR) were determined from lithologic logs based on downhole log and continuous core data for six sites at four continental margins around the Southern Ocean. Total MAR was calculated at Ocean Drilling Program (ODP) Site 1095 on the margin of the Antarctic Peninsula and ODP Site 1165 on the margin of Prydz Bay, Antarctica. Carbonate and noncarbonate (terrigenous) MAR were calculated for ODP Sites 1123 and 1124 east of New Zealand and Sites 1168 and 1172 west and southeas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 59 publications
(92 reference statements)
0
10
0
Order By: Relevance
“…Considering the substantial increase in sedimentation documented in 2010 and 2011 in these cores, the benthic foraminiferal density alone did not account for compaction or dilution [ 9 ]. To account for compaction and dilution, a benthic foraminiferal accumulation rate (BFAR) approach was taken to determine changes from the down-core section to the upper section of each record [ 39 , 40 ]. BFAR were reported as the number of foraminifera per unit area over time (fcm −2 yr −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Considering the substantial increase in sedimentation documented in 2010 and 2011 in these cores, the benthic foraminiferal density alone did not account for compaction or dilution [ 9 ]. To account for compaction and dilution, a benthic foraminiferal accumulation rate (BFAR) approach was taken to determine changes from the down-core section to the upper section of each record [ 39 , 40 ]. BFAR were reported as the number of foraminifera per unit area over time (fcm −2 yr −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The dating of Site 1165 is based on a combination of diatom and radiolarian biostratigraphies [ Bohaty and Whitehead , 2001; Whalen and Lazarus , 2001; Florindo et al , 2003b] and magnetostratigraphy [ Florindo et al , 2003b]. The base of the hole is dated at about ∼21 Ma, and there is a long‐term trend of decreasing sedimentation rates from the bottom to the top of the hole [ Handwerger and Jarrard , 2003]. The quality of preservation of diatoms and radiolarians decreases below 608 mbsf, and no diatoms are found below 754 mbsf, making dating difficult in this lower part of the hole.…”
Section: Datingmentioning
confidence: 99%
“…No IRD older than 10 Ma was found at Site 751, approximately 400 km north of Site 744 [ Breza , 1992]. In general, IRD appears earlier at sites which are closer to the continent, reflecting the location of iceberg melting, probably because sea surface temperatures fell and the polar front moved northward through time [ Handwerger and Jarrard , 2003].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because mineralogical heterogeneity is usually the major source of MAR errors, this high‐resolution approach reduces the 95% confidence limits for average chron MAR by >95%. For example, Handwerger and Jarrard [2003] showed that MST‐based carbonate MAR for Site 1124 was much more continuous and precise than that based on discrete carbonate and density analyses. Furthermore, the resulting analysis of brief time periods enables more precise identification of timing of major changes in mass accumulation rates, guiding the choice of intervals for longer‐term averaging.…”
Section: Methodsmentioning
confidence: 99%